Executive compensation: facts - Gian Luca Clementi; Thomas F. Cooley (Fondazione Eni Enrico Mattei (FEEM), 2010)
In this paper we describe the important features of executive compensation in the US from 1993 to 2006. Some confirm what has been found for earlier periods and some are novel. Notable facts are that: the compensation distribution is highly skewed; each year, a sizeable fraction of chief executives lose money; the use of security grants has increased over time; the income accruing to CEOs from the sale of stock increased; regardless of the measure we adopt, compensation responds strongly to innovations in shareholder wealth; measured as dollar changes in compensation, incentives have strengthened over time, measured as percentage changes in wealth, they have not changed in any appreciable way.
Keywords: G34; J33; M52; 330; CEO; Pay-Performance Sensitivity; Stock; Options